Network and internetwork security principles and practice - Stallings, William (Prentice Hall ; IEEE, 1995)
In a recent attack on the Texas A&M computer complex, which consists of over 12,000 interconnected PCs, workstations, minicomputers, mainframes, and servers, a well-organized team of hackers were able to take virtual control of the complex. Having broken in by running password-cracking programs, the intruders then modified login software to enable them to capture additional passwords of users logging on to systems.